2004
DOI: 10.2223/jped.1184
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to inhalant and food allergens in Brazilian atopic children by <i>in vitro</i> total and specific IgE assay. Allergy Project - PROAL

Abstract: Fonte financiadora: Pharmacia do Brasil (doou kits para dosagens).Artigo submetido em 015.12.03, aceito em 03.03.04. AbstractObjective: To determine the frequency of sensitization to inhalant and food allergens in children seen at Brazilian allergy services.Patients and methods: Total and specific IgE serum levels to inhalant and food allergens (RAST, UniCAP ® Pharmacia) were measured in 457 children accompanied in pediatric allergy services and in 62 control children age matched. RAST equal or higher than cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 17 publications
1
18
0
4
Order By: Relevance
“…1,3 The first Brazilian Allergy Project (PROAL I) study was carried out in 2004 with the objective of documenting the sensitization rates to the major allergens in Brazilian allergic children. 4 This was the first study of its kind, which contributed to better understanding of regional differences and enabled comparison with other countries. During the past decade, the prevalence of asthma and allergic diseases in children and adolescents has increased.…”
Section: Increased Sensitization To Several Allergens Over a 12-year mentioning
confidence: 99%
See 1 more Smart Citation
“…1,3 The first Brazilian Allergy Project (PROAL I) study was carried out in 2004 with the objective of documenting the sensitization rates to the major allergens in Brazilian allergic children. 4 This was the first study of its kind, which contributed to better understanding of regional differences and enabled comparison with other countries. During the past decade, the prevalence of asthma and allergic diseases in children and adolescents has increased.…”
Section: Increased Sensitization To Several Allergens Over a 12-year mentioning
confidence: 99%
“…4 Thus, a sample of 430 children and adolescents was recruited to estimate the frequency of sensitization, with a sampling error of 4.0% and a 95% confidence level, using an estimated dimensioning frequency variable in 73.0%. 4 To compare allergic patients to the non-allergic group, it was necessary to evaluate, in the previous study, the percentage of sensitization of an allergen that was prevalent and in similar magnitudes between allergy and non-allergy groups. A two-way comparison test was used to estimate the difference in allergic sensitization.…”
Section: Increased Sensitization To Several Allergens Over a 12-year mentioning
confidence: 99%
“…In a study from Vietnam, allergic sensitization was observed in 36.9% of the males and 31% of the females and the most common allergens were B. tropicalis, D. pteronyssinus, D. Farinae and cockroaches [20]. In a study from Brazil, allergic sensitization rates for some foods were as follows: 29.5% for fish, 24.4% for egg, 23.1 % for cow milk, 20% for wheat, 14% for peanut, and 4.8-11.8 % for soybean [21]. In another study from Korea, allergic sensitization rates for some foods were as follows: 51.5% for egg, 31.2% for cow milk, 16.2% for peanut, and 15.4% for soybean [22].…”
Section: Discussionmentioning
confidence: 98%
“…In Brazil, Guimarães et al (2015) collected information from parents of pre-school children with allergy to different foods and found the following: milk (42.7%), pork (11.6%), fruits (10.9%), chocolate (9.4%), and eggs (9.2%). Investigating the prevalence of sensitivity to food allergens in children in Brazil, Naspitz et al (2004) reported reaction to food allergens in subjects tested for IgE sensitivity, indicating a significantly greater proportion of sensitive individuals than non-sensitive ones. Table 3 shows the prevalence of tree nuts allergy in patients from several countries.…”
Section: Food Allergy × Tree Nutsmentioning
confidence: 99%